Khảo sát địa điện về hình thái cấu trúc trầm tích bở rời vùng chiêm trũng Ninh Bình - Giảng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2000)
Application of geoelectrical measurements to’thestudy of near-surface sedimentary structuralmorphology in the Ninhbinh summer rice_fields